2010
DOI: 10.20965/jaciii.2010.p0722
|View full text |Cite
|
Sign up to set email alerts
|

An Artificial Intelligence Approach to Develop a Time-Series Prediction Model of the Arc Furnace Resistance

Abstract: The control scheme of an arc furnace electrode positioning system aims to deliver an optimum stable reaction zone below the electrodes by maintaining a fixpoint resistance. However, because of random movement of melted materials during melting period, the resistance of the arc furnace changes randomly. As a result, the electrodes have to move accordingly to obtain a fix-point resistance. Moreover, it is often found that the arc furnace resistance changes very fast and it is impossible for the electrode to trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…An accurate wind and load prediction is a key factor that ensures a robust performance of the EMPRS. In several studies conducted earlier, it was demonstrated that an accurate forecasting system can be developed for the short-term (up to 15 minutes) forecasting of wind and load conditions [23]- [27]. An integration of wind and load forecasting in the EMPRS will allow to implementing the load curtailment in advance, and thus avoid system blackouts as demonstrated below.…”
Section: A Wind and Load Predictionmentioning
confidence: 99%
See 2 more Smart Citations
“…An accurate wind and load prediction is a key factor that ensures a robust performance of the EMPRS. In several studies conducted earlier, it was demonstrated that an accurate forecasting system can be developed for the short-term (up to 15 minutes) forecasting of wind and load conditions [23]- [27]. An integration of wind and load forecasting in the EMPRS will allow to implementing the load curtailment in advance, and thus avoid system blackouts as demonstrated below.…”
Section: A Wind and Load Predictionmentioning
confidence: 99%
“…From (27), during high wind conditions, the excess power (P EX ) is consumed by the battery storage system as follows:…”
Section: B Load Schedulingmentioning
confidence: 99%
See 1 more Smart Citation